2022
DOI: 10.1038/s41467-022-32192-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-fluorinated non-solvating cosolvent enabling superior performance of lithium metal negative electrode battery

Abstract: The growth of dendrites on lithium metal electrodes is problematic because it causes irreversible capacity loss and safety hazards. Localised high-concentration electrolytes (LHCEs) can form a mechanically stable solid-electrolyte interphase and prevent uneven growth of lithium metal. However, the optimal physicochemical properties of LHCEs have not been clearly determined which limits the choice to fluorinated non-solvating cosolvents (FNSCs). Also, FNSCs in LHCEs raise environmental concerns, are costly, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 57 publications
1
47
0
Order By: Relevance
“…However, the structurally dense SEIs can act as resistive interfacial layers that hinder the fast electrochemical performance. As the formation of SEI is common dynamic behavior in battery systems, a new strategy should be proposed to yield high ion-conductive and stable interlayers, thereby enabling long-term stability and fast charge transfer kinetics. , Furthermore, electrochemical interfaces even undergo severe reconstructions involving compositional change and crystallographic domain transformation (e.g., grain boundary formation, and amorphization) during electrocatalysis. ,, To resolve and understand the aforementioned interfacial behaviors, recent studies propose some strategies guiding the reconstruction process in a controllable direction to break from the conventional catalyst design path. In these cases, surface reconstruction sometimes generates unique active sites with enhanced catalytic activity and selectivity for specific products.…”
Section: Discussionmentioning
confidence: 99%
“…However, the structurally dense SEIs can act as resistive interfacial layers that hinder the fast electrochemical performance. As the formation of SEI is common dynamic behavior in battery systems, a new strategy should be proposed to yield high ion-conductive and stable interlayers, thereby enabling long-term stability and fast charge transfer kinetics. , Furthermore, electrochemical interfaces even undergo severe reconstructions involving compositional change and crystallographic domain transformation (e.g., grain boundary formation, and amorphization) during electrocatalysis. ,, To resolve and understand the aforementioned interfacial behaviors, recent studies propose some strategies guiding the reconstruction process in a controllable direction to break from the conventional catalyst design path. In these cases, surface reconstruction sometimes generates unique active sites with enhanced catalytic activity and selectivity for specific products.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the actual cycle of the battery, most of the electrolyte decomposition products come from EC. [24,54] In addition, electrolyte engineering requires not only wide ECW performance obtained by -F and -CN functional groups substitution, but also finely modulate molecular structure of electrolyte composition introducing partially fluorinated and locally polar -CHF 2 function group [50] or design non-fluorinated non-solvating cosolvent [34] to improve electrode stability, cycling performance and sufficient solvation for fast transport.…”
Section: Discussionmentioning
confidence: 99%
“…The results show that the oxidation potentials of the above 68 solvents calculated by using the SMD model to describe the solvent energy of systems are in good agreement with the experimental values (with the calculated MAE lower than 0.68 V vs. Li + /Li). For example, Lim et al [34] found that 3 M solv LiFSI 1,2-Dimethoxy ethane (DME): Furan-(1: 2) electrolyte can exhibit high oxidation potential (≈4.50 V vs. Li + /Li) by linear sweep voltammetry (LSV), which is in good agreement with our calculated intrinsic values using the SMD model (DME: 4.90 V vs. Li + /Li, Furan: 4.73 V vs. Li + /Li). Martins et al [35] also reported previously that SMD method can provide more accurate solvation free energy calculation results (with a lowest average mean unsigned error) compared with PCM and COSMO methods for specific alcohol-based molecule systems.…”
Section: Proposing a Thermodynamic Cycle Approach Including Solvent E...mentioning
confidence: 99%
“…In the battery community, qNMR has been proven to be a powerful tool to investigate the electrolyte composition and its evolution upon cycling in various systems. 4 , 5 , 6 , 7 , 8 Herein, the procedure of qNMR for electrolyte quantification and the recently developed electron transfer numbers (ETNs) fitting method are documented and elucidated.…”
Section: Before You Beginmentioning
confidence: 99%